The construction of a slave identity: an examination of the dual identity of indentured labourers across the Western Pacific. (3rd September 2019) - Jones, Grant
ABSTRACT: The examination of indentured labour in the Western Pacific has been reported as pure historiography, without the guidance of an explicit theoretical framework. It has concluded that indenture in this case does not meet its own definition of slavery. However, this analysis is highly dated in as much as it is narrowly institutionalist in perspective, relying on legalistic points of distinction, such as the existence of a labour contract. To challenge this established wisdom a new-institutionalist history is conjured from existing social an economic theory. This enables the topic to be brought into the business and organisation disciplines. The examination demonstrates the promotion of a dual identity, which cast native labourers as free labourers, while instantiating norms readily identifiable with slavery. These norms served to encourage low-status natives into acceptance of the disciplines of the plantation and other businesses as part of the natural order, but proved unsustainable over the longer term as a broader range of life choices emerged.